2019
DOI: 10.1371/journal.pone.0221076
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Helicobacter pylori infection and obesity in Chinese adults: A systematic review with meta-analysis

Abstract: BackgroundObesity is highly prevalent worldwide. More and more studies have been conducted on the relationship between H. pylori infection and obesity or overweight. But the relationship between them is controversial in the literatures and there is no comprehensive evidence for the correlation.AimTo evaluate the prevalence of H. pylori infection in Chinese adult subjects who received routine physical examinations and the relationship between H. pylori and obesity.MethodsLiteratures on H. pylori infection and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 50 publications
4
43
2
3
Order By: Relevance
“…16 Regarding association of H. pylori infection with gall stones, it was more common in H. pylori negative cases (82%) as compared to H pylori positive cases (76%). The results were similar to that of another study in which the prevalence of gallstones in H pylori positive cases was lower than in the H pylori-negative cases (odds ratio, 0.653) 11 In our study, fibrosis was present in most of the H pylori positive cases (94%) whereas it was less (79%) in non-infected patients proving its association with chronic cholecystitis. In another study, 36% cases of H pylori positive group had fibrosis but the same frequency was also seen in H pylori negative group and therefore no statistically significant difference was noted regarding fibrosis between both the groups 16 When analyzed statistically, comparison of patients with H pylori positive and H pylori negative was not found significant in any of the findings.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…16 Regarding association of H. pylori infection with gall stones, it was more common in H. pylori negative cases (82%) as compared to H pylori positive cases (76%). The results were similar to that of another study in which the prevalence of gallstones in H pylori positive cases was lower than in the H pylori-negative cases (odds ratio, 0.653) 11 In our study, fibrosis was present in most of the H pylori positive cases (94%) whereas it was less (79%) in non-infected patients proving its association with chronic cholecystitis. In another study, 36% cases of H pylori positive group had fibrosis but the same frequency was also seen in H pylori negative group and therefore no statistically significant difference was noted regarding fibrosis between both the groups 16 When analyzed statistically, comparison of patients with H pylori positive and H pylori negative was not found significant in any of the findings.…”
Section: Discussionsupporting
confidence: 91%
“…Hyperlipidemia, sedentary lifestyle, low fiber, high fat diet, metabolic syndrome and diabetes are the commonest causative factors of gallstone formation leading to cholecystitis. 4 In recent years, few studies from Middle East 5 and Asia (China, 4,6,7 , Iran, 8,9, India 10,11 ) have identified a new causative agent "H pylori" which plays a role in gall stone formation leading to cholecystitis. The initial study dates back to 1996 by Kawaguchi et al 12 who incidentally discovered a microorganism resembling H pylori from a cholecystectomy specimen.…”
Section: Original Articlementioning
confidence: 99%
“…Moreover, Ad36 infection was shown to induce acute and chronic in ammation leading to angiogenesis in fatty tissues (49). Another systematic review by Xu et al concludes that Helicobacter pylori infection may be a risk factor for the development of obesity (50). However, a causal relationship cannot be established due to the nature of the study design of the included studies.…”
Section: Viral Infections May Induce Obesitymentioning
confidence: 99%
“…The OR value showed that H. pylori ‐positive subjects tended to be obese at a risk of 1.20 (95% CI: 1.13‐1.28). However, the study did not establish a causal relationship between H. pylori infection and obesity 18 . Whether there is a positive or a negative correlation between H. pylori and obesity remains to be answered.…”
Section: Discussionmentioning
confidence: 82%